Feasibility and safety of modified en-bloc resection in endoscopic thyroid surgery via bilateral areolar approach – long-term institutional analysis ten years after surgery - Xie, Qiuping; Ma, Junjie; Du, Yu; Liu, Lianxuan; Zhu, Ruiying; Liu, Danni; Wang, Ping; Yu, Xing (Frontiers in Endocrinology, 2024)
This study aimed to introduce a new modified en-bloc resection method and evaluate its feasibility and safety in endoscopic thyroid surgery via bilateral areolar approach (BAA).Methods: Papillary thyroid carcinoma (PTC) patients who underwent lobectomy and ipsilateral central node dissection (CND) via the BAA approach were retrospectively reviewed. Their clinical characteristics and outcomes were evaluated, including operative duration, lymph node yield (LNY), surgical complications, recurrence rate, and metastasis rate, over a ten-year follow-up period. Simultaneous lobectomy and CND were performed in the modified en-bloc group, whereas lobectomy was performed first, followed by CND in the conventional group.The study included 108 patients in the modified en-bloc group and 213 in the conventional group. There were no significant differences in gender, age, tumor locations, tumor dominant nodule size, or the incidence of concomitant Hashimoto thyroiditis when comparing clinicopathologic characteristics. The comparison of operative duration (P = 0.14), blood loss (P = 0.13), postoperative hospital stay (P = 0.58), incidence of transient vocal cord paralysis (P = 0.90) and hypocalcemia (P = 0.60) did not show any differences. The mean LNY achieved in the central compartment of the modified en-bloc group (7.5 ± 4.5) was significantly higher than that in the conventional group (5.6 ± 3.6). Two patients in the modified en-bloc group and two in the conventional group experienced metastasis after surgery during the ten-year follow-up (1.8% vs. 0.9%, P = 0.60). The learning curve analysis showed a significant decrease in operative duration after the 25-35 th cases for modified en-bloc resection.The modified en-bloc resection method in endoscopic thyroid surgery via BAA is a technically feasible and safe procedure with excellent cosmetic outcomes for selective PTC patients.